Prevalence and correlates of Helicobacter pylori infection among under-five children, adolescent and non-pregnant women in Nepal: Further analysis of Nepal national micronutrient status survey 2016. - Suresh Mehata; Kedar Raj Parajuli; Narayan Dutt Pant; Binod Rayamajhee; Uday Narayan Yadav; Ranju Kumari Mehta; Priya Jha; Neha Mehta; Meghnath Dhimal; Dipendra Raman Singh (Public Library of Science (PLoS), 2021)
Most of the Helicobacter pylori infections occur in developing countries. The risk factors for H. pylori infections are poverty, overcrowding, and unhygienic conditions, which are common problems in under-privileged countries such as Nepal. Despite having a high risk of H. pylori infections, no national level study has been conducted to assess prevalence and correlates of H. pylori infection in Nepal. Therefore, we hypothesized that micronutrients such as iron, vitamin B12 deficiency, socio-economic status, and nutritional status correlate with the prevalence of H. pylori infection in Nepal. We studied prevalence and correlates of H. pylori infection among under-five children, adolescents aged 10-19 years and married non-pregnant women aged 20-49 years using data from the Nepal National Micronutrient Status Survey 2016 (NNMSS-2016). H. pylori infection was examined in stool of 6-59 months old children and 20-49 years old non-pregnant women whereas the rapid diagnostic kit using blood sample was used among adolescent boys and girls. Prevalence of H. pylori infection was 18.2% among 6-59 months old children, 14% among adolescent boys and 16% among adolescent girls aged 10-19 years; and 40% among 20-49 years non-pregnant women. Poor socioeconomic status, crowding, and unhygienic condition were found to be positively associated with higher incidence of H. pylori infections. No significant correlation was observed between nutritional and micronutrients status (iron or risk of folate deficiency) with H. pylori infection. Findings from this study suggest that poverty-associated markers are primary contributors of H. pylori infections in Nepalese communities. To control acquisition and persistence of H. pylori infection in Nepal, we suggest improved management of safe drinking water and implementation of sanitation and hygiene programs, with a focus on those of lower socioeconomic status.